2006
DOI: 10.1111/j.1600-0560.2006.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin and β‐catenin expression patterns in malignant melanoma assessed by image analysis

Abstract: Središnja medicinska knjižnicaPećina-Šlaus, N., Žigmund, M., Kušec, V., Nikuševa Martić, T., Čačić, M., AbstractBackground. We investigated the expression of E-cadherin and beta-catenin in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…Specifically, mutations in -catenin have been detected in both melanoma biopsies and melanoma cell lines (Larue and Delmas 2006). These findings are reinforced by immuno-histochemical studies showing that -catenin staining is frequently observed in primary melanomas, but is less abundant in metastatic melanomas (Pecina-Slaus, Zigmund et al 2007;De Panfilis, Ferrari et al 2009) and appears to be inversely correlated with the Clark stage (Pecina-Slaus, Zigmund et al 2007). In both cases, -catenin is observed predominantly at the cell membrane and in the cytoplasm (PecinaSlaus, Zigmund et al 2007;Tucci, Lucarini et al 2007;De Panfilis, Ferrari et al 2009).…”
Section: Alterations In the Wnt/β-catenin Pathway In Melanomasupporting
confidence: 60%
“…Specifically, mutations in -catenin have been detected in both melanoma biopsies and melanoma cell lines (Larue and Delmas 2006). These findings are reinforced by immuno-histochemical studies showing that -catenin staining is frequently observed in primary melanomas, but is less abundant in metastatic melanomas (Pecina-Slaus, Zigmund et al 2007;De Panfilis, Ferrari et al 2009) and appears to be inversely correlated with the Clark stage (Pecina-Slaus, Zigmund et al 2007). In both cases, -catenin is observed predominantly at the cell membrane and in the cytoplasm (PecinaSlaus, Zigmund et al 2007;Tucci, Lucarini et al 2007;De Panfilis, Ferrari et al 2009).…”
Section: Alterations In the Wnt/β-catenin Pathway In Melanomasupporting
confidence: 60%
“…We could clearly demonstrate that β-catenin is mainly distributed in the cytoplasm of melanoma cells in vivo and under culture conditions. Studies of Maelandsmo et al and Pecina-Slaus et al support this finding (21,30). In only 5.6 or 6.4%, respectively, of the analyzed samples nuclear localization of β-catenin was observed by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 60%
“…Cell lysate (5-40 µg) was separated on 10% SDS-PAGE gels and subsequently blotted onto a PvDF membrane. After blocking with 3% BSA/PBS the membrane was incubated for 16 h with one of the following antibodies: anti-β-catenin (1 in 3000 dilution) (Sigma), antihypophosphorylated β-catenin (35-50) (1 in 200 dilution) (Acris, Hiddenhausen, Germany), anti-hypophosphorylated β-catenin (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) (1 in 200 dilution) (upstate), anti-β-cateninphospho 41/45 (1 in 500 dilution) (Cell Signaling), anti-β-catenin phospho S33 (1 in 500 dilution), anti-β-catenin phospho S37 (1 in 500 dilution), anti-β-catenin phospho T41 (1 in 500 dilution), anti-β-catenin phospho S45 (1 in 500 dilution), (Abcam, Cambridge, UK), and anti-β-actin (1 in 5000 dilution) (Sigma).…”
Section: Transfection Experiments and Luciferase Measurementsmentioning
confidence: 99%
“…In consistence with the observation, cytoplasmic/nuclear β-catenin expression has been reported to be reduced upon progression 47,48,[67][68][69] . However, in the individual studies, the limited sample size and potentially biased patients' selection failed to satisfy the minimal REporting recommendations for tumour MARKer prognostic studies (REMARK) guidelines 70 .…”
Section: Localizing β-Catenin: a Technical Challenge In Clinicmentioning
confidence: 57%